If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 2x + 5(-2x + 17) Reorder the terms: 13 = 2x + 5(17 + -2x) 13 = 2x + (17 * 5 + -2x * 5) 13 = 2x + (85 + -10x) Reorder the terms: 13 = 85 + 2x + -10x Combine like terms: 2x + -10x = -8x 13 = 85 + -8x Solving 13 = 85 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 13 + 8x = 85 + -8x + 8x Combine like terms: -8x + 8x = 0 13 + 8x = 85 + 0 13 + 8x = 85 Add '-13' to each side of the equation. 13 + -13 + 8x = 85 + -13 Combine like terms: 13 + -13 = 0 0 + 8x = 85 + -13 8x = 85 + -13 Combine like terms: 85 + -13 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| 150p-105+13p=58 | | l+4=16 | | -30=-3+1y | | 13x+72=-23x | | (4ab)(4ab)(4ab)= | | 4x^2+6x+2=90000 | | 3c+5+c=-6+4c+8 | | 16=7+n | | 17+-9y=-3+7y | | 6n=243 | | 8cos^2(x)-2=0 | | 15/-2h=15/12 | | 14+x=6 | | 4b^2-28b-120=0 | | 5c^2=35c | | x=4-5(6) | | x^3=93 | | 6-3v=3v-18 | | 4g+20=6t-13 | | 15x+6=75 | | 8-(-25+4)= | | 10x+19=3x+201 | | -2/7*x+6+1/7*x=18 | | 3/x+3=5/2x+6+2/x-2 | | 3x-3-4=x | | 2j+4=10j | | 3x-3-2=x | | -3(6b)+5b+8= | | 7x+2=6x-7 | | 3x-3-1.75=x | | 2x/3-6=5x | | -25*2= |